Workplace Ethics and Job Commitment Among Secretarial Staff in the Public Sector, Delta State, Nigeria - Onojaife Caroline (Review of Human Resources, Organizational Change, and Economic Impact, 2025)
This study examined the impact of workplace ethics on job commitment among secretarial staff in the public sector of Delta State, Nigeria. Specifically, it assessed the effects of integrity, respect for organizational policies, and accountability on job commitment. A descriptive research design was used, with a target population of 10,943 secretarial staff across 25 local government areas. A sample of 368 respondents was selected using Krejcie and Morgan’s formula. Data were collected via a structured questionnaire, yielding a response rate of 86.14% (317 out of 368). The reliability of the instrument was confirmed with a Cronbach Alpha of 0.81. Descriptive and inferential statistical techniques, including Pearson correlation analysis, were used to analyze the data. Findings indicated that integrity, respect for organizational policies, and accountability all had significant positive effects on job commitment. The study recommends regular ethics training, transparent policy enforcement mechanisms, and participatory approaches to policy development to enhance job commitment.